2016
DOI: 10.3988/jcn.2016.12.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the wnt/β-Catenin Signaling Pathway in Polymyositis, Dermatomyositis and Duchenne Muscular Dystrophy

Abstract: Background and PurposeThe wnt/β-catenin signaling pathway plays a critical role in embryonic development and adult-tissue homeostasis. Recent investigations implicate the importance of wnt/β-catenin signaling in normal wound healing and its sustained activation being associated with fibrogenesis. We investigated the immunolocalization and activation of wnt/β-catenin in polymyositis (PM), dermatomyositis (DM), and Duchenne muscular dystrophy (DMD).MethodsImmunofluorescence staining and Western blot analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Several differentially regulated KEGG pathways were identified. The Wnt signaling pathway, which was indicated to be upregulated in patients with DM-associated ILD [ 39 ], and the cyclic adenosine monophosphate signaling pathway, which has been known to antagonize pulmonary fibrosis activated by phosphodiesterase 4 [ 40 ], were involved in DM-ILD-MDA5 Ab(+) exosomes when compared to both HC and DM-nonILD-MSA16(-) exosomes, suggesting that these signaling pathways may be unique to ILD, particularly in the DM-ILD-MDA5 Ab(+) subset. Transforming growth factor- β signaling, which was reported to be upregulated in muscle samples with sporadic inclusion body myositis [ 41 ], and mTOR signaling may be potential pathways of autoimmune diseases [ 42 ] and were included in the CTGs of DE miRNAs in the DM-nonILD-MSA16(-) exosomes, suggesting that these pathways may contribute to the pathogenesis of DM.…”
Section: Discussionmentioning
confidence: 99%
“…Several differentially regulated KEGG pathways were identified. The Wnt signaling pathway, which was indicated to be upregulated in patients with DM-associated ILD [ 39 ], and the cyclic adenosine monophosphate signaling pathway, which has been known to antagonize pulmonary fibrosis activated by phosphodiesterase 4 [ 40 ], were involved in DM-ILD-MDA5 Ab(+) exosomes when compared to both HC and DM-nonILD-MSA16(-) exosomes, suggesting that these signaling pathways may be unique to ILD, particularly in the DM-ILD-MDA5 Ab(+) subset. Transforming growth factor- β signaling, which was reported to be upregulated in muscle samples with sporadic inclusion body myositis [ 41 ], and mTOR signaling may be potential pathways of autoimmune diseases [ 42 ] and were included in the CTGs of DE miRNAs in the DM-nonILD-MSA16(-) exosomes, suggesting that these pathways may contribute to the pathogenesis of DM.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the key genes with an important role, we next used panther analysis to find key pathways in which the lincRNA target genes were involved. Our study showed targets of the lincRNAs were part of essential processes of WNT signaling, TGF-β, and Apoptotic inducing pathways ( Figure 2 c,d); some of these pathways are well known to be important in various myopathies and dystrophies [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 82%
“…Major characteristics of muscle biopsies of the dystrophic hearts include necrotic muscle fibres surrounded by macrophages, lymphocytes, mast cells and myofibroblasts [ 31 , 42 , 50 , 51 ], supporting that DDC results from imbalance between muscle fibre necrosis, inflammatory response and myofibroblasts regeneration [ 30 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. At the molecular level, the fibrotic process is regulated by a complex network of signalling pathways that includes inflammatory cells (lymphocytes, macrophages, mast cells), inflammatory factors (IL, TNF-a, NF-kB) peptides (ANG2, endothelin 1 (ET-1), aldosterone), growth factors (Transforming growth factor (TGF-β), connective tissue growth factor (CTGF), platelet-derived growth factor (PDGF)), ions (Ca2+), oxidative stress molecules (NADPH, NOX, LOX…), adhesion molecules (integrins, osteopontin), matrix metalloproteinases (MMP), and immunoproteasome ( Figure 2 ) [ 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. These interdependent factors favour the activation and proliferation of myofibroblasts [ 66 , 67 , 68 ].…”
Section: Overview Of the Fibrotic Process In Ddcmentioning
confidence: 99%